Struktur dan Anatomi Organisasi - N, Nurjanah; Putri, Anjellie Dasviana; Ritonga, Nurhayani; Z, Zulqarnain; Sukatin, M. (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study examines the structure and anatomy of organizations. The approach used was a qualitative approach with a literature study. The study results show that Organizational structure can affect organizational performance because through an efficient organizational structure is able to improve efficiency and productivity, then organizational structure also affects decision making and motivation of workers.The role of organizational anatomy is to improve efficiency, improve productivity, identify innovation, increase improving communication, as well as optimizing resources.